2010
DOI: 10.1007/s11145-009-9224-4
|View full text |Cite
|
Sign up to set email alerts
|

Literacy coaching as a component of professional development

Abstract: Current debates concerning effective professional development for teachers of early reading have focused on the potential benefits of a literacy coach in providing sustained support and guidance for teachers' learning from a professional development program. In this study, we compare the response of first-grade teachers to a model of professional development that did or did not include a literacy coach (i.e., PD Coach or PD No Coach) by examining teachers' attitudes toward professional development, their instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 30 publications
3
66
0
1
Order By: Relevance
“…The aspect of the seminars and workshops which involves the invited experts to be the speakers or trainers as one of the contributive elements in the way how teachers learn is in line with what is stated by Carlisle and Berebitsky (2011) who explain that the presence of experts can help teachers to broaden their knowledge related to their problemsolving activity in the teaching practice. Still in line with this, a number of studies done by Garet, Porter, Desimone et al (2001), Richards & Farrel (2005), Madya (2007), Smith & Gillespie (2007), Munera et.al.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The aspect of the seminars and workshops which involves the invited experts to be the speakers or trainers as one of the contributive elements in the way how teachers learn is in line with what is stated by Carlisle and Berebitsky (2011) who explain that the presence of experts can help teachers to broaden their knowledge related to their problemsolving activity in the teaching practice. Still in line with this, a number of studies done by Garet, Porter, Desimone et al (2001), Richards & Farrel (2005), Madya (2007), Smith & Gillespie (2007), Munera et.al.…”
Section: Discussionsupporting
confidence: 61%
“…This is supported by various studies which have been done related to the exemplary profile of professional English teachers and their experiences in developing their professionalism (Garet et al, 2001;Kolo, 2006;Anugerahwati, 2009;Vo & Nguyen, 2010;Fisher et al, 2010;Mustafa, 2011;Carlisle & Berebitsky, 2011;Amin, 2013;Husein, 2013;Priajana, 2015). In Indonesian context, the notion of teachers' professionalism has also been given much attention.…”
Section: Introductionmentioning
confidence: 81%
“…Finally, we developed a model for professional development based on a directive model of coaching (Deussen, Coskie, Robinson, & Autio, 2007 ). Labeled in many ways, including expert consultant (Gersten, Morvant, & Brengelman, 1995 ), technical coach (Denton & Hasbrouck, 2009 ), expert mentor (Carlisle & Berebitsky, 2010 ), and sounding board and advisor (Sperry, 2008 ), directive coaches often assume the role of knowledgeable specialists and "are assertive about what instructional practices teachers must implement" (Ippolito, 2010 , p. 165). Often referred to as an outside-in approach (Sheridan, Edwards, Marvin, & Knoche, 2009 ), directive coaching has been shown to improve teachers' practices (Pianta, Mashburn, Downer, Hamre, & Justice, 2008 ).…”
Section: Coaching Supportmentioning
confidence: 99%
“…Marks and Printy (2003) concluded student achievement and teaching improved when teachers shared instructional leadership with principals and took on transformational leadership roles. Although some studies indicate no positive relationship between coaching and student achievement, a few found an increase in student achievement associated with coaching (Biancarosa et al, 2010;Carlisle & Berebitsky, 2010;Elish-Piper & L'Allier, 2011;Matsumura, Garnier, Correnti, Junker, & Bickel, 2010;Ross, 1992). Perhaps most striking, Biancarosa et al (2010) found value-added effects of the Literacy Collaborative coaching program over 4 years, with achievement increasing in kindergarten through second grade and the magnitude of the program's effects growing with each year of implementation.…”
Section: Instructional Leadership Teaching and Learningmentioning
confidence: 99%